Economic Potential of the Process of Polyphenol Extraction from Cocoa Pod Husk (Theobroma cacao L.) Using the Ultrasonic-Assisted Extraction Method - Rachel Mega Jessica Putri (Candela Edutech Indonesia, 2025)
Polyphenols are phytochemical substances in plants that can work as antioxidants which can inhibit oxidation and the formation of free radicals. Polyphenols can be found in almost all plants, like cocoa pod husk. This research was conducted to determine the feasibility of the polyphenol extraction process from cocoa pod husk using the ultrasonic-assisted extraction method from an economic perspective based on the effect of drying the material and the type of solvent used. The solvents used were distilled water, 96% ethanol and 95% methanol on materials without drying and materials with drying to a water content of ±11%. From the research results, optimum extraction results were obtained for the samples by drying the material and using distilled water solvent at an extraction time of 60 minutes, which produced a yield of 7.95% and a phenolic content of 22.01% or 220.1248 mg gae/g. From an economic perspective, this process provides a profit of IDR 539,683.05/kg. The extract yield and economic benefits obtained from the ultrasonic-assisted extraction method are greater than from the maceration method